The Goldilocks Dilemma in Acute Ischemic Stroke - Tansy, Aaron P.; Liebeskind, David S. (Frontiers in Neurology, 2013)
Despite the advent of and exciting advances in novel endovascular therapies, t-PA remains the only proven treatment for acute ischemic stroke to date. Although a variety of reasons likely underlie why past trials of endovascular strategies have been unsuccessful, we address in this perspective piece one critical unknown for which a solution is undoubtedly necessary if future ones are to meet with success: determination and selection of patients that are “just right” for endovascular treatments, or the Goldilocks dilemma. Key clinical criteria highlighted in past trials may help provide a solution to this critical problem. However, for them to do so, we propose that they must be applied in service of a model that accounts for the nuanced, dynamic nature of acute ischemic stroke better than the prevailing “time is brain” model. We provide and examine three clinical cases to illustrate this proposal towards solving the Goldilocks dilemma and advancing treatment in acute ischemic stroke. Further, we address our field’s ongoing challenge and mission in the meantime to best care for the “not-so-right” patients, by far the majority of the affected stroke population.